Interpreting complex forensic DNA evidence - Taupin, Jane Moira (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
Interpreting Complex Forensic DNA Evidence is a handy guide to recent advances--and emerging issues--in interpreting complex DNA evidence and profiles for use in criminal investigations. In certain cases, DNA cannot be connected to a specific biological material such as blood, semen or saliva. How or when the DNA was deposited may be an issue. However, the possibility of generating DNA profiles from touched objects, where there may not be a visible deposit, has expanded the scope and number of exhibits submitted for DNA analysis. With such advances, and increasing improvements in technological capabilities in testing samples, this means it is possible to detect ever smaller amounts of DNA. There are also many efforts underway to seek was to interpret DNA profiles that are sub-optimal--either relative to the amount required by the testing kit and, potentially, the quality of the obtained sample. Laboratories often use enhancements in order to obtain a readable DNA profile. The broad-reaching implications of improving DNA sensitivity have led to this next, emerging generation of more complex profiles. Examples partial profiles that do not faithfully reflect the proposed donor, or mixtures of partial DNA from multiple people. A complexity threshold has been proposed to limit interpretation of poor-quality data. Research is now addressing the interpretation of transfer of trace amounts of DNA. Complex issues are arising in trial that need to be reconciled as such complexity has added challenges to the interpretation of evidence and its introduction or dismissal in certain cases in the courts. Interpreting Complex Forensic DNA Evidence provides tools to assist the criminal investigator, forensic expert, and legal professional when posed with a DNA result in a forensic report or testimony. The result--and any associated statistic--may not reveal any ambiguity, complexity, or the assumptions involved in deriving it. Questions from resolved criminal cases are posed, and the relevant forensic literature, are provided for the reader to assess a DNA result and any associated statistic. Case studies included throughout illustrate concepts and emphasize the need for conclusions in the forensic report that are data-driven and supported by the data.
1. Introduction - Complex Versus Simple DNA Evidence 2. Types of DNA Profiles 3. Interpretation of Profiles 4. Transfer 5. History of Exhibit 6. Quality 7. Controversies
OCLC-licensed vendor bibliographic record.
Keywords: LAW / Forensic Science; LAW / Criminal Law / General; SCIENCE / Life Sciences / Genetics & Genomics; DNA fingerprinting; Forensic genetics; DNA -- Analysis; Criminals -- Identification